Simulating an intra-fraction adaptive workflow to enable PTV margin reduction in MRIgART volumetric modulated arc therapy for prostate SBRT - Snyder, Jeffrey; Smith, Blake; Aubin, Joel St.; Shepard, Andrew; Hyer, Daniel (Frontiers in Oncology, 2024)
This study simulates a novel prostate SBRT intra-fraction re-optimization workflow in MRIgART to account for prostate intra-fraction motion and evaluates the dosimetric benefit of reducing PTV margins.VMAT prostate SBRT treatment plans were created for 10 patients using two different PTV margins, one with a 5 mm margin except 3 mm posteriorly (standard) and another using uniform 2 mm margins (reduced). All plans were prescribed to 36.25 Gy in 5 fractions and adapted onto each daily MRI dataset. An intra-fraction adaptive workflow was simulated for the reduced margin group by synchronizing the radiation delivery with target position from cine MRI imaging. Intra-fraction delivered dose was reconstructed and prostate DVH metrics were evaluated under three conditions for the reduced margin plans: Without motion compensation (no-adapt), with a single adapt prior to treatment (ATP), and lastly for intra-fraction reoptimization during delivery (intra). Bladder and rectum DVH metrics were compared between the standard and reduced margin plans.As expected, rectum V18 Gy was reduced by 4.4 ± 3.9 %, D1cc was reduced by 12.2 ± 6.8 % ( 3.4 ± 2.3 Gy), while bladder reductions were 7.8 ± 5.6 % for V18 Gy , and 9.6 ± 7.3 % (3.4 ± 2.5 Gy) for D1cc for the reduced margin reference plans compared to the standard PTV margin. For the intrafraction replanning approach, average intra-fraction optimization times were 40.0 ± 2.9 seconds, less than the time to deliver one of the four VMAT arcs (104.4 ± 9.3 seconds) used for treatment delivery. When accounting for intra-fraction motion, prostate V36.25 Gy was on average 96.5 ± 4.0 %, 99.1 ± 1.3 %, and 99.6 ± 0.4 for the non-adapt, ATP, and intra-adapt groups, respectively. The minimum dose received by the prostate was less than 95 % of the prescription dose in 84 %, 36 %, and 10 % of fractions, for the non-adapt, ATP, and intra-adapt groups, respectively.Intra-fraction re-optimization improves prostate coverage, specifically the minimum dose to the prostate, and enables PTV margin reduction and subsequent OAR sparing. Fast re-optimizations enable uninterrupted treatment delivery.